2019
DOI: 10.3892/ol.2019.10572
|View full text |Cite
|
Sign up to set email alerts
|

miR‑296‑3p targets APEX1 to suppress cell migration and invasion of non‑small‑cell lung cancer

Abstract: Non-small-cell lung cancer (NSCLC) is the most common cause of cancer-associated mortality worldwide. MicroRNAs (miRs) are a class of small non-coding RNAs that are commonly dysregulated in human cancer. The aim of the current study was to evaluate the effect of miR-296-3p on the cell migration and invasion of NSCLC. Pairs of tumor tissues and para-cancerous tissues (n=50) were collected from patients with NSCLC, and the expression of miR-296-3p was analyzed by reverse transcription-quantitative polymerase cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…The role of various lncRNA in regard to lung tumor development and progression is still subject for further study. As for the role of miRNA, it was found that the overexpression of miR-296-3p reduced the level of phosphorylation in this pathway without reducing mRNA expression by targeting apurinic/apyrimidinic endodeoxyribonuclease 1 (APEX1), therefore possibly inhibiting the pathway's progression particularly in NSCLC [241]. Additionally, miR-296-3p has been reported to have lower levels of expression in comparison to normal lung epithelial cells, and it played a role in inhibiting NSCLC cell proliferation as well as cisplatin sensitivity by targeting C-X3-C motif chemokine receptor 1(CX3CR1) which is upstream of PI3K signaling [242].…”
Section: Pi3k/akt/mtormentioning
confidence: 99%
“…The role of various lncRNA in regard to lung tumor development and progression is still subject for further study. As for the role of miRNA, it was found that the overexpression of miR-296-3p reduced the level of phosphorylation in this pathway without reducing mRNA expression by targeting apurinic/apyrimidinic endodeoxyribonuclease 1 (APEX1), therefore possibly inhibiting the pathway's progression particularly in NSCLC [241]. Additionally, miR-296-3p has been reported to have lower levels of expression in comparison to normal lung epithelial cells, and it played a role in inhibiting NSCLC cell proliferation as well as cisplatin sensitivity by targeting C-X3-C motif chemokine receptor 1(CX3CR1) which is upstream of PI3K signaling [242].…”
Section: Pi3k/akt/mtormentioning
confidence: 99%
“…Moreover, HDAC3 overexpression is documented to promote CRC proliferation and invasion [ 8 ]. MicroRNAs-296-3p (miR-296-3p) serves as a suppressor in malignancies including non-small-cell lung cancer, choroidal melanoma and glioblastoma [ 9 11 ]. Widely, it is implied that miR-296 is a suppressor of CRC cell progression and tumor growth [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The complex role of miR-296-3p as an oncogene or tumor suppressor has been described in several cancer types but has rarely been described in PTC [24][25][26][27] . Here, we found that the expression of miR-296-3p was significantly decreased in PTC tissues compared with adjacent tissues using qRT-PCR ( Fig.…”
Section: Mir-296-3p Suppresses Ptc Cell Proliferation and Motilitymentioning
confidence: 99%